Soft skills training for battery gigafactories 4.0 - Vincent, Ann-Sofi; Norberg, Anders; Bowskill, Nicholas (Proceedings of the International Conference on Networked Learning, 2024)
We probably all agree that well developed soft skills are essential for any human to have, both in private social life and the workplace. However, it has recently come before our eyes (read below) that soft skills maybe even more in demand than hard technical skills, even for high-tech machine operators in Industry 4.0. In this roundtable, we want to discuss how to integrate soft skills training in any course at any level of education. The participants inputs and contributions in discussion are essential for ongoing massive education and training development on the European level.